Entrepreneurial leadership self-efficacy: a focus on Malaysian student entrepreneurial leaders - Bagheri, Afsaneh; Lope Pihie, Zaidatol Akmaliah; Krauss, Steven Eric (Societe de Physique et d'Histoire Naturelle de Geneve, 2013)
The main purpose of this study is to provide a deeper understanding of university students’ perceptions toward their capabilities of leading a new venture. More specifically, this study attempted to examine how university students’ perceptions toward their capabilities of leading a new venture develop and the sources that shape their perceptions of entrepreneurial leadership self-efficacy. This study employed a qualitative research method to investigate university students’ entrepreneurial leadership self-efficacy. It involved a sample of fourteen university undergraduate students who were purposefully selected to participate in this research. Analysis of semi-structured interviews indicates that the students perceived themselves as capable of leading a business. Moreover, it is through leading university entrepreneurship projects and teams that the students’ entrepreneurial abilities and in particular, entrepreneurial leadership self-efficacy improves. The findings also revealed that entrepreneurial leadership self-efficacy is a multi-dimensional construct consisting of different components that shape the students’ overall perceptions toward their abilities to lead new ventures. Students’ entrepreneurial leadership self-efficacy originates from different sources including: management self-efficacy, opportunity identification self-efficacy, relationship self-efficacy, tolerance self-efficacy, and learning self-efficacy. Implications of the findings for entrepreneurship education, research and theory development are discussed.